Hungary--a market for products from developing countries - International Trade Centre UNCTAD/GATT. (Geneva : The Centre, 1985)
This book is on Hungary economic reforms to modernize both the structure and management of the economy. It examines foreign trade patterns, trade with developing countries; Hungary's foreign trade system, techniques for approaching the Hungarian market and information for foreign businessmen.
oo 21/01/2019
Loans
Keywords: Hungary; Developing countries